Uterine Myxoid Leiomyosarcoma with Tumor Embolism Extending into the Right Atrium - Hiromi Imai; Hiroshi Yagi; Kaoru Okugawa; Hironori Kenjo; Tatsuhiro Ohgami; Yoshiaki Kawano; Eisuke Kaneki; Akimasa Ichinoe; Kazuo Asanoma; Hideaki Yahata; Kenzo Sonoda; Hiroaki Kobayashi; et al. (Hindawi Limited, 2015)
Uterine myxoid leiomyosarcoma (MLMS) is an extremely rare variant of uterine leiomyosarcoma; only 56 cases were reported from 1982 to 2013. Uterine MLMS is characterized by a myxoid appearance and highly malignant behavior. We herein report a case involving a 65-year-old woman with uterine MLMS with a large tumor embolism that reached the right atrium. A total abdominal hysterectomy, bilateral salpingooophorectomy, and tumor embolism resection with the use of a heart-lung machine were performed. Epirubicin-ifosfamide chemotherapy in the adjuvant setting led to reductions in both the tumor emboli and peritoneal dissemination. The patient retained a good quality of life for 10 months after the initial surgery. She then developed progressive disease despite treatment with pazopanib. She died of her disease 14 months after the initial surgery. Although complete surgical resection of the tumor is desirable, tumor reduction surgery followed by adjuvant chemotherapy might help to retain a good quality of life. This is the first reported case of a primary uterine MLMS with tumor emboli.